A spatial analysis of air pollution and environmental inequality in Beijing, 2000–2010. Issue 14 (6th December 2019) - Ma, Jing; Liu, Bochu; Mitchell, Gordon; Dong, Guanpeng
Abstract : Whilst air pollution is a major problem in China, little is known about how it is distributed socially and how such distributions are changing over time. We use a fine-grained population census and air quality data for 2000 and 2010 to explore socio-spatial and temporal inequalities in air pollution for Beijing, using distributional analyses and spatial regression models. We find that environmental inequalities exist with respect to measures of social disadvantage, such as hukou migrant status, very young children (0–4  years), and the elderly (≥65  years). Our temporal analysis reveals that environmental inequality increases for migrants and the elderly, who bear a disproportionate and increasing share of declining air quality from 2000 to 2010. Regression results emphasise the spatial and temporal variations in environmental inequality, as the associations between air pollution and social demographics differ between different urban zones of Beijing; and their geographic patterns change significantly over time.